Knowledge donation, hoarding, and hiding behaviors of high performers: Mediation role of deviant silence - Muhammad Waseem Bari; Qurratulain Khan; Francesca Di Virgilio (European Research on Management and Business Economics)
High performance punishment occurs when organizations distribute more work responsibilities to their best performers without offering supplementary compensation or recognition. The lack of appreciation through additional rewards creates burnout and employee resentment in such situations. Drawing on social exchange theory, this study examines the impact of high-performance punishment on high performers’ knowledge behaviors: knowledge donation, hoarding, and hiding. Besides, how deviant silence mediates these relationships. The sample data are collected from 534 employees of IT organizations across countries, and data are analyzed using the PLS-SEM technique with the Smartpls 4 software. The results show that high-performance punishment positively impacts knowledge hoarding and hiding behaviors but does not significantly impact knowledge donation. Deviant silence partly mediates the relationship between high-performance punishment and knowledge behaviors. It is deduced that although high-performance punishment promotes negative knowledge behaviors, but it does not affect willingness to donate knowledge until an employee indulges in deviant silence. The paper concludes with practical implications for organizations and submissions for future studies on managing high-performing employees.